Internalisasi Nilai-Nilai Karakter Masyarakat Islam Madinah Zaman Nabi SAW pada Lembaga Pendidikan Islam - Yasser, Rayyan (Al-Qiyadi Jurnal Manajmen Pendidikan Islam, 2024)
Islamic educational institutions are not limited solely to the field of education but also serve a social function to enhance user satisfaction. The application of the societal character values of the Islamic community of Madinah during the time of the Prophet (peace be upon him) can increase the effectiveness and productivity of an Islamic educational institution. This study proposes six character values. The research employs a literature review method by searching for sources, reading, and examining relevant materials related to the theme. After the examination, the findings are analyzed and subsequently written into a scientific article. The results of this study reveal that the six character values, namely, brotherhood, social equality; social cooperation; deliberation; participative and professionalism; universal social justice; social responsibility; and promoting good and preventing harm can be implemented in Islamic educational institutions through various approaches, behaviors, and activities. By consistently internalizing these six values with ongoing efforts and regular evaluation, the management and operations of Islamic educational institutions will become increasingly effective and productive